Unconditional life : the postwar international law settlement - Otomo, Yoriko (Oxford : Oxford University Press, 2016)
Looking at how international law regulates, and is itself influenced by, technology and risk, this book illustrates how and why international law has been unable to properly deal with large-scale technological risk.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 14, 2016).
Keywords: Technology and law; Technology -- Risk assessment; International law; Law